2015
DOI: 10.1007/s11684-015-0426-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-β2 glycoprotein I antibodies in complex with β2 glycoprotein I induce platelet activation via two receptors: apolipoprotein E receptor 2′ and glycoprotein I bα

Abstract: Anti-β2 glycoprotein I (anti-β2GPI ) antibodies are important contributors to thrombosis, especially in patients with antiphospholipid syndrome (APS). However, the mechanism by which anti-β2GPI antibodies are involved in the pathogenesis of thrombosis is not fully understood. In this report, we investigated the role of anti- β2GPI antibodies in complexes with β2GPI as mediators of platelet activation, which can serve as a potential source contributing to thrombosis. We examined the involvement of the apolipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…The activation-signaling pathways of platelets consequent to the presence of β2-GPI and anti-β2-GPI antibodies are mediated by interaction with phospholipids on the cell surface (phosphatidylserine, phosphatidylethanolamine) or with platelet membrane receptors [5,8]. Their combination in complexes contributes to platelet activation in an apolipoprotein E receptor 2′ (apoER2′) and glycoprotein Ib-α (GPIb-α)-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation-signaling pathways of platelets consequent to the presence of β2-GPI and anti-β2-GPI antibodies are mediated by interaction with phospholipids on the cell surface (phosphatidylserine, phosphatidylethanolamine) or with platelet membrane receptors [5,8]. Their combination in complexes contributes to platelet activation in an apolipoprotein E receptor 2′ (apoER2′) and glycoprotein Ib-α (GPIb-α)-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Their combination in complexes contributes to platelet activation in an apolipoprotein E receptor 2′ (apoER2′) and glycoprotein Ib-α (GPIb-α)-dependent manner. This interaction induces the activation of the platelet signaling pathway, expressed by p38 mitogen-activated protein kinase (MAPK) phosphorylation, and the prothrombotic phenotype, expressed by GP IIb/IIIa conformational change, P-selectin expression and thromboxane B2 production [8]. This interaction induces the activation of the platelet signaling pathway, expressed by p38 mitogen-activated protein kinase (MAPK) phosphorylation, and the prothrombotic phenotype, expressed by GP IIb/IIIa conformational change, P-selectin expression and thromboxane B2 production [8].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activation and microparticle (MP) release were induced upon incubation with 0.1 U/ml of thrombin (Sigma-Aldrich) or anti-β2GPI/β2GPI complex for 60 min at 37 °C with gentle agitation. Anti-β2GPI/β2GPI complex (anti-β2GPI:β2GPI = 5/50 μg/ml or 10/100 μg/ml) was dissolved in Tris-buffered saline (TBS) as previously described [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study reported on anti-β2GPI-dependent platelet activation by LRP8 receptors and the mitogen-activated protein kinase 14 (MAPK14) pathway [ 3 ]. Anti-β2GPI antibodies are also known to activate human endothelial cells [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in vitro studies suggest that Toll-like receptor (TLR) 4 and annexin A2 (a phospholipid-binding protein involved in endothelial activation and in the regulation of the coagulation cascade), possibly through reciprocal interactions, behave as β2GPI cell surface receptors and promote activation of the endothelium as well as of circulating leukocytes and platelets [50]. TLR 1, 2, 6 and apolipoprotein E receptor 2 might also redundantly recognise β2GPI on the cell surface [50][51][52].…”
Section: Antiphospholipid Antibodiesmentioning
confidence: 99%